Standard care and investigational drugs in the treatment of myelofibrosis - Daniela Barraco; Margherita Maffioli; Francesco Passamonti (BioExcel Publishing Ltd, 2019)
Myelofibrosis (MF) is a heterogeneous disorder characterized by splenomegaly, constitutional symptoms, ineffective hematopoiesis, and an increased risk of leukemic transformation. The ongoing research in understanding the pathophysiology of the disease has allowed for the development of targeted drugs optimizing patient management. Furthermore, disease prognostication has significantly improved. Current therapeutic interventions are only partially effective with only allogeneic stem cell transplant potentially curative. Ruxolitinib is the only approved therapy for MF by the US Food and Drug Administration. However, despite efficacy in reducing splenomegaly and controlling symptomatology, it is not associated with consistent molecular or pathologic responses. Drug discontinuation is associated with a dismal outcome. The therapeutic landscape in MF has significantly improved, and emerging drugs with different target pathways, alone or in combination with ruxolitinib, seem promising.